An analysis of forecasting abilities of DSGE and Treshold VAR models - Kuchta, Michal; Quang, Tran Van; Janíčko, Martin, 1983-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
In this Thesis, small to medium scale DSGE model for Czech republic incorporating set of frictions and rigidities is derived, and estimated by Bayesian techniques. Subsequent Impulse response and Shock decomposition analysis evaluate properties of this model. Model is then matched to empirical data and estimated on Czech major economic time series. Forecasting performance of this models is opposed by Bayesian Threshold VAR and plain Bayesian VAR Models. Forecasting exercise considers a variety of settings and its evaluation is judged upon RMSE providing simple ranking of inquired models.
Vedoucí práce: Van Quang Tran
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses